2022
DOI: 10.1093/g3journal/jkac001
|View full text |Cite
|
Sign up to set email alerts
|

Genome of the parasitoid waspDinocampus coccinellaereveals extensive duplications, accelerated evolution, and independent origins of thelytokous parthenogeny and solitary behavior

Abstract: Dinocampus coccinellae (Hymenoptera: Braconidae) is a generalist parasitoid wasp that parasitizes >50 species of predatory lady beetles (Coleoptera: Coccinellidae), with thelytokous parthenogeny as its primary mode of reproduction. Here we present the first high quality genome of D. coccinellae using a combination of short and long read sequencing technologies, followed by assembly and scaffolding of chromosomal segments using Chicago+HiC technologies. We also present a first-pass ab initio and a refere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…It is generally believed that thelytoky evolved from arrhenotoky in Hymenoptera ( Cook 1993 ; Adachi-Hagimori et al, 2011 ; Ma et al, 2014 ; Sethuraman et al, 2022 ). A recent study suggested two independent origins for thelytokous Dinocampus coccinellae from the ancestral arrhenotokous strain ( Sethuraman et al, 2022 ). However, in the process of evolution, thelytokous and arrhenotokous modes have reached different outcomes ( Smith and Maynard-Smith, 1978 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that thelytoky evolved from arrhenotoky in Hymenoptera ( Cook 1993 ; Adachi-Hagimori et al, 2011 ; Ma et al, 2014 ; Sethuraman et al, 2022 ). A recent study suggested two independent origins for thelytokous Dinocampus coccinellae from the ancestral arrhenotokous strain ( Sethuraman et al, 2022 ). However, in the process of evolution, thelytokous and arrhenotokous modes have reached different outcomes ( Smith and Maynard-Smith, 1978 ).…”
Section: Discussionmentioning
confidence: 99%